A national survey of window‐opening behavior in United States homes. (23rd September 2021) - Morrison, Glenn; Cagle, John; Date, Gauri
Abstract: Air exchange is among the most important building parameters influencing indoor air quality and energy use. Over 18‐month period we surveyed over 3800 individuals to generate a contemporary, nationwide measure of window‐ and door‐opening behavior. We also identified influences of demographics, climate, and region. For the entire survey, including all seasons and geographic regions, 43.9% of respondents said that at least one window was open the day prior to taking the survey. Greater window‐opening frequency was associated with having a lower income, living in attached homes or apartments, renting, lack of air conditioning, or being Asian or Hispanic. People living in the west and north open windows considerably more frequently and longer than those in the southeastern US. Window‐opening frequency and duration increases with outdoor temperature until a maximum occurs at 18–21°C. At temperatures greater than this, window frequency decreases. The pattern roughly holds, by region, with the peak occurring at a lower temperature in the NW (12°C), and a higher temperature in the SW and SE. The frequency of door opening is roughly half that of window opening with similar, but not identical, demographic, regional, and climate associations.